1976
DOI: 10.1017/s0022172400024669
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of foot-and-mouth disease: the lung as an additional portal of entry of the virus

Abstract: 'Mention of a trademark or a proprietary product does not constitute a guarantee or warranty of the product by the United States Department of Agriculture, and does not imply its approval to the exclusion of other products that may also be suitable.' SUMMARY Donor cattle infected with foot and mouth disease (FMD) virus subtype 01 were used to expose experimental cattle. The pharyngeal virus growth and viraemia patterns after contact exposure were quite different from those obtained after intranasal inoculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 14 publications
0
23
0
1
Order By: Relevance
“…It causes viremia, and there is evidence that spread through the bloodstream is important in the dissemination of the virus within the animal (48). Wild-type isolates of FMDV do not bind to HS, but upon tissue culture passaging, SP variants with the ability to bind to HS arise (18,43).…”
Section: Discussionmentioning
confidence: 99%
“…It causes viremia, and there is evidence that spread through the bloodstream is important in the dissemination of the virus within the animal (48). Wild-type isolates of FMDV do not bind to HS, but upon tissue culture passaging, SP variants with the ability to bind to HS arise (18,43).…”
Section: Discussionmentioning
confidence: 99%
“…Infected cattle also aerosolize large amounts of virus, which can infect other cattle in addition to other species (438). A number of studies have suggested that the lung or pharyngeal areas are the sites of initial virus replication (72,79,444), with rapid dissemination of the virus to oral and pedal epithelial areas (72,79,444), possibly mediated by cells of monocyte/macrophage origin (72). In cattle experimentally infected via aerosol, it was found, by in situ hybridization (ISH), that within the first 24 h, virus was present in respiratory bronchiolar epithelium, subepithelium, and interstitial areas of the lung (74).…”
Section: Pathogenesismentioning
confidence: 99%
“…Moreover, the ability of FMDV to replicate in tissues of the upper respiratory system, demonstrated in early reports (7) and widely confirmed later using more sensitive approaches, identified the soft palate and pharynx as sites of FMDV replication and persistence in ruminants (8,9). Sutmoller and McVicar further expanded their initial findings to include the lung as an additional portal of virus entry (10), although many researchers considered the evidence for both sites of entry to be controversial. Recently, a detailed description of the previremic stages after experimental aerosol infection of cattle confirmed these early results, identifying both the pharynx and lung as primary sites for viral entry (11).…”
mentioning
confidence: 94%